2001
DOI: 10.1007/s005860100309
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in patients with adolescent idiopathic scoliosis: a matched follow-up at least 20 years after treatment with brace or surgery

Abstract: No results on long-term outcome in terms of health-related quality of life (HRQL) have previously been presented for patients treated for adolescent idiopathic scoliosis. A consecutive series of patients with adolescent idiopathic scoliosis, treated between 1968 and 1977 before the age of 21, either with distraction and fusion using Harrington rods [surgical treatment group (ST), n=156; 145 females and 11 males] or with a brace [brace treatment group (BT), n=127; 122 females and 5 males] were followed at least… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
248
4
8

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 292 publications
(267 citation statements)
references
References 43 publications
(49 reference statements)
7
248
4
8
Order By: Relevance
“…In line with our results, other studies also found no major impact of gender [7,15,20], Cobb angle [7,9] and curve type [2,7,9] on HRQoL after treatment.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In line with our results, other studies also found no major impact of gender [7,15,20], Cobb angle [7,9] and curve type [2,7,9] on HRQoL after treatment.…”
Section: Discussionsupporting
confidence: 93%
“…Climent et al [7] also found that patients treated with a brace were less satisfied with management than patients treated surgically. A similar trend was seen in a study by Danielsson et al [9] on HRQoL after follow-up of at least 20 years in patients treated with a brace and patients treated surgically; they reported a more negative effect of the treatment period on patients treated with a brace than on patients treated surgically, but in that study different measures were used than in our study. Furthermore, in the present study, patients treated only surgically had highest scores on the self-image/ appearance domain and on the single-item general health; although significant, these differences were rather small (respectively, 0.2 points on a 5-point scale and 7 points on a 100-point scale).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Another bias mentioned in nearly all epidemiologic studies is that they do not consider the psychological impact of scoliosis on children, although it has been described extensively in current literature [47][48][49]. Young girls particularly, but also boys, that have deformities might feel embarrassed when being examined in school.…”
Section: Discussionmentioning
confidence: 99%
“…Cosmesis for the adolescent patient is an important factor for self-confidence, as studies have shown evidence of psychological distress in this population due to cosmetic concerns [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%